Needs assessment for a training program of parents to promote increased parent involvement in mathematics education - Çeziktürk, Özlem. (Thesis (M.A.) - Bogazici University. Institute of Social Sciences, 1997., 1997)
In this study, it was aimed to provide the initial data to be used in the establishment of a new parent training program which aims to increase the effective and efficient parent involvement in mathematics education and to identify the factors behind parent involvement. Sample was fonned by 337 selected students from one Imam Hatip Lycee, one Eight Year Elementary School, one Anadolu Lycee, and one Private College; 257 parents of these students; and 17 mathematics teachers from these schools. Regarding the demographic and specific characteristics of subjects, current status in parent involvement, awareness about the need for parent involvement, perceived adequacy of parent involvement, willingness to participate to the training program was detennined by three questionnaires. These questionnaires had four parts basically the same which differ with respect to the status of the subjects. Data was cross-tabulated and analyzed by t-test and one-way ANOVA when appropriate. The domains of the parent involvement was identified as effective communication among the groups (ECG), effective home study with child (EHSC), mathematics study with fun (MF), factors behind achievement and underachievement in mathematics (FMA), the amount and the type of reasonable financial support (FS), ,attitudes towards mathematics (ATM) , active involvement (AI) attitudes towards parent involvement (API). Among students, specifically school type and math-perfonnance; and among parents, the level of education, the level of English proficiency, income level, occupation type, and school type of their children were identified as related with their needs in parent involvement domains. Anadolu Lycee students were identified as more aware about the needs towards parent involvement in general and needs towards parent involvement domains specifically. Teachers were seen as the most aware group about parent involvement and how it should be. In addition, teachers were the group who saw parents as the least adequate in parent involvement in all domains. Parents generally meet with teachers at PT As and help to their children before exams. Parents were seemed to be aware of the need for parent involvement in the domains ECG, MF, AI, and API whereas teachers identified the need for parent involvement under the domains MF, FMA, and FS. Parents were seeing themselves as adequate in the domain ofFS only. Students indicated their parents need for training on the domains of ECG, EHSC, and MF. Meanwhile, teachers identified the need for training of parents on all domains in mathematics education. To sum up, the majority of the sample was seemed to support a training program to promote effective and efficient parent involvement.
Keywords: Education -- Parent participation -- Turkey.; Parent and child.; Parent-teacher relationships.; Mathematics -- Study and teaching (Elemantary) -- Turkey.